2015
DOI: 10.1177/0267659115589399
|View full text |Cite
|
Sign up to set email alerts
|

Duration of conventional cardiopulmonary resuscitation prior to extracorporeal cardiopulmonary resuscitation and survival among adult cardiac arrest patients.

Abstract: More than half of all patients who received ECPR survived to 30 days. Longer duration CCPR was associated with reduced survival within 2 weeks, but not at 30 days.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…In advanced therapies, such as extracorporeal assisted CPR, CPR duration should be considered as a component of the protocol [4, 27, 29, 30]. For example, Reynolds et al showed that the optimal time for considering an alternative method to conventional CPR is within 15 min [27].…”
Section: Discussionmentioning
confidence: 99%
“…In advanced therapies, such as extracorporeal assisted CPR, CPR duration should be considered as a component of the protocol [4, 27, 29, 30]. For example, Reynolds et al showed that the optimal time for considering an alternative method to conventional CPR is within 15 min [27].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, when CCPR is prolonged, even if adequately delivered, the probability of return of spontaneous circulation (ROSC) progressively decreases. In one study, Mosca et al reported that CPR maneuvers lasting for more than 45 min were associated with hospital survival of less than 2%, most of the patients dying without achieving ROSC [4]. In this setting, in particular for patients who have received the best possible resuscitation (i.e., short no-flow time, bystander CPR, shockable rhythms refractory to defibrillation), there would be a high possibility of good cardiac and neurological recovery in case of ROSC, which make these patients as the best potential candidates for extracorporeal cardiopulmonary resuscitation (ECPR).…”
Section: Introductionmentioning
confidence: 99%